Palmyras Reichtum durch weltweiten Handel. Achäologische Untersuchungen im Bereich der hellenistischen Stadt Band 2: Kleinfunde - Schmidt-Colinet, Andreas (Holzhausen, 2013)
Final publication of an international excavation project in Palmyra/Syria. Publicaation of so called small finds of an hellenistic-roman caravan building: pottery (incl. natural science analyses), amphorae, lamps, glass. metal, coins, animal bones.